2002
DOI: 10.1152/ajpregu.00502.2001
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal reflex regulation of the glottis depends on central glycinergic inhibition in the rat

Abstract: Dutschmann, Mathias, and Julian F. R. Paton. Trigeminal reflex regulation of the glottis depends on central glycinergic inhibition in the rat. Am J Physiol Regulatory Integrative Comp Physiol 282: R999-R1005, 2002; 10.1152/ ajpregu.00502.2001.-In an unanesthetized decerebrate in situ arterially perfused brain stem preparation of mature rat, strychnine (0.05-0.2 M) blockade of glycine receptors caused postinspiratory glottal constriction to occur earlier, shifting from early expiration to inspiration. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 26 publications
5
23
0
Order By: Relevance
“…pump muscles) targets. Pharmacologic blockade of glycine receptors in the neonatal or adult respiratory network caused a paradoxic inspiratory glottal constriction, although rhythmic network activity persisted (16,17). This result parallels the upper airway response to severe hypoxia demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…pump muscles) targets. Pharmacologic blockade of glycine receptors in the neonatal or adult respiratory network caused a paradoxic inspiratory glottal constriction, although rhythmic network activity persisted (16,17). This result parallels the upper airway response to severe hypoxia demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…In one study, gasping during severe hypoxia was reported to be accompanied by a massive reduction or total abolishment of postinspiratory motor activity destined for the upper airway (11,14). Recent studies showed that an obvious absence of postinspiratory motor activity does not necessarily mean a cessation of the activity of postinspiratory motor neurones (15)(16)(17). We found that postinspiratory neurones (including adductor motor neurones) discharged earlier in the respiratory cycle during the inspiratory phase.…”
mentioning
confidence: 63%
See 3 more Smart Citations